Inequality of Opportunities Among Children : How Much Does Gender Matter? - Hoyos, Alejandro; Narayan, Ambar (World Bank, Washington, DC, 2017)
Authors apply a decomposition method to a measure of inequality of opportunities among children (the human opportunity index) to examine the question of how much does gender of a child contribute to inequality in access to critical services that should be available as basic minimum opportunities to all children. Authors use a database of 47 countries for which Demographic and Health Survey (DHS) data is available during 2003-2010, four indicators for opportunities and a limited set of circumstances or characteristics of the child. On the average and for most countries, the contribution of gender of the child to inequality of opportunity in two measures of school attendance and immunization tends to be low and much below the contribution of household factors such as economic status and urban/rural location. In a few countries, however, gender still plays a more substantial role in influencing a child's access to a particular service. Preliminary evidence also suggests that inequalities and contributions of gender to inequality across opportunities are correlated, particularly for opportunities in the same sector.